Strategi Manajemen Pelaksanaan Pengajuan Klaim Non Kapitasi BPJS Kesehatan Di Klinik Asiki Boven Digoel Papua Selatan - Jayawijaya, Firman; Hidayat, Dasrun; Rachman, Arif (ProBisnis : Jurnal Manajemen, 2025)
This research is entitled "Management Strategy for the Implementation of BPJS Health Non-Capitation Claim Submission at Asiki Clinic, Boven Digoel, South Papua ’ which is motivated by the high rejection rate of BPJS Health non-capitation claims at Asiki Clinic, which reached 48 cases from January 2021 to December 2023. This high rejection rate indicates weaknesses in human resource management, the absence of clear SOPs, and the limitations of the information technology system used. This study aims to analyse the implementation of non-capitation claim submission in terms of inputs, processes, and outputs and formulate management strategies to improve the effectiveness of claims management at Asiki Clinic. Using qualitative methods, this study found that Asiki Clinic lacks trained claims officers, does not have adequate SOPs, and uses ineffective IT systems. The claims process was often disrupted by a lack of training and the absence of a structured management strategy, resulting in incomplete claims files and high rejections. Recommendations include developing and training human resources, developing SOPs, optimising information technology, and improving communication with BPJS Kesehatan. Effective implementation of management strategies is expected to improve the quality of health services, reduce claim rejections, and ensure the financial sustainability of Asiki Clinic. This study contributes to the health management literature and can serve as a model for other primary healthcare facilities facing similar problems in remote areas.